Analisis Perbandingan Kesiapan Guru terhadap Perubahan Kurikulum Di Sekolah Menengah Atas Kota Pontianak - Evi Tri Prihatini; Meri Meri; Trisya Sumiati; Aunurrahman Aunurrahman; Waneri Waneri (Journal on Education, 2024)
Curriculum changes require educational units to respond to new things quickly and responsively. The role of teacher readiness in implementing the new curriculum is very significant. This research aims to observe whether there is a difference in the level of readiness between teachers in public and private schools in Pontianak City, with 30 people as a sample, divided into 15 teachers from SMA Negeri 11 Pontianak and 15 teachers from SMA Private Muhammadiyah 1 Pontianak. Data was collected through a survey using descriptive statistical analysis through a closed questionnaire. Based on the results of statistical tests carried out with the IBM SPSS 25 application, the significance value of 0.000 was obtained, there is a significant difference between teacher readiness for curriculum changes in public and private high schools, where teacher readiness at SMAN 11 Pontianak is 77% which is included in the category While only 70% of SMAS Muhammdiyah 1 Pontianak is in the Medium category. Differences in teacher readiness for curriculum changes include understanding the characteristics and structure of the curriculum with a difference of 10%, readiness for learning plans a difference of 5%, readiness of facilities and infrastructure with a difference of 10%, and readiness for learning assessment planning a difference of 13%. Based on the research results, it can be concluded that the level of teacher preparedness at SMA Negeri 11 Pontianak is higher than at SMAS Muhammadiyah 1 Pontianak.